Stability Analysis and Fracture Patterns of Hard Main Roof in Longwall Top Coal Caving with Large Mining Height - Jinkai Liu; Chunyuan Li; Yaoyu Shi; Yong Zhang (Shock and Vibration)
In order to study the fracture patterns of hard main roof in longwall top coal caving (LTCC) with large mining height, a two-dimensional physical similarity model was created to simulate the mining process of No. 8100 large mining height face in Tongxin coal mine, China. The results show that there are three positions of broken line in hard main roof presented with the advance of longwall face, and the underground pressure induced by hard main roof fracturing presents the effect of superposition of large and small periods. It is found that there are two fracture patterns of main roof during the mining process: composite structure of lower cantilever beam and upper voussoir beam with hard main roof and composite structure instability of lower and upper voussoir beam with hard main roof. The underground pressure induced by these two fracture patterns is also analyzed by building mechanical models. In the end, the hydraulic fracture technique is introduced to presplit the main roof and weaken the effect of dynamic loads induced by composite structures instability.